Kontribusi Yayasan Insan Cendikia Cemerlang dan Peranan Kepala Desa Mekar Sari Kecamatan Deli Tua yang Positif bagi Pelaku Usaha Peternakan Ulat Hongkong sesuai Undang-Undang No. 41 Tahun 2014 Perubahan atas Undang-Undang No 18 Tahun 2009 tentang Petern - Dewi Robiyanti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Investment in Hong Kong caterpillar farming has a strategic role in supporting food security and the national economy. Law No. 41 of 2014 concerning Amendments to Law No. 18 of 2009 concerning Animal Husbandry and Animal Health provides a legal basis for investment in the livestock sector. This article discusses assistance and contributions to investment in Hong Kong caterpillar farming from the perspective of regulation, economic benefits, and challenges faced. The results of the study indicate that clear policy support and investment incentives can encourage the growth of the Hong Kong caterpillar farming industry in Indonesia.